Actividad amilásica durante la germinación del grano de trigo. Estudio electroforético - Luciani, J.A; Dubois de Trecco, M.E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The alpha and beta's amilase activities in extracts of seeds of wheat (Buck Manantial) matured and at differents stages of germination was determined. In the matured seeds the main part of the activity belongs to beta amilasa. During germination alpha amilasa's activity increases until the sixth day. The disc electrophoresis in poliacrilamide and specific stains in extracts of riped seeds show two bands of quicklyY movement activity. while the seeds extracts at differents periods of germination show the apparition of seven additional bands of slower movements.